Value-at-risk under ambiguity aversion - Rossella Agliardi (Financial Innovation, 2018)
This study explored the effects of ambiguity on the calculation of Value-at-Risk (VaR) using a mathematical model based on the theory of Choquet-Brownian processes. It was found that while a moderate degree of ambiguity aversion yields a higher value for VaR and Expected Shortfall (ES), the result can be reversed in a deeply ambiguous environment. Additionally, some sufficient conditions are provided for the preservation of this effect under various forms of risk aggregation. This study offers a new perspective to full awareness on capital requirement calculation as requested by international regulation.
Keywords: 650; Choquet-Brownian motion; Risk measures; Ambiguity aversion